Platelet-Rich Plasma Applications, The Past 5 Years: A Review Article - Michael Buontempo; Lina Alhanshali; Jerry Shapiro; Kristen Sicco; Michael Garshick (European Medical Journal, 2023)
Platelet-rich plasma (PRP) is autologous plasma with a platelet concentration that is on average five times greater than baseline, and has been extensively investigated for its potential applications across various medical fields, including orthopaedics, dermatology, wound healing, maxillofacial surgery, and others. This review article aims to provide an overview of PRP's applications and evidence over the past 5 years in randomised controlled trials. Many studies demonstrate PRP's effectiveness in reducing pain and improving functional outcomes, while others report no significant differences compared to alternative treatments or placebo. Across various studies, several key limitations exist, such as small sample sizes, short follow-up durations, and lack of standardisation in PRP preparation methods, highlighting the need for research to further establish PRP's effectiveness in these clinical applications. The article also discusses the different classification systems for PRP, and underscores the importance of understanding the components that influence clinical outcomes, as well as noting the growth of PRP in the marketplace. Overall, while studies exist demonstrating the clinical utility of PRP, standardised reporting is required to determine its full potential, as well as optimal preparation and administration strategies.